Removal of arsenic, methylene blue, and phosphate by biochar/AlOOH nanocomposite - Zhang, Ming; Gao, Bin (Chemical engineering journal (Lausanne, Switzerland : 1996), 2013)
•Biochar/AlOOH nanocomposite was produced from biomass through pyrolysis.•AlOOH particles on biochar surfaces are nanosized.•Biochar matrix is mesoporous with average pore size of 50nm.•Biochar/AlOOH nanocomposite effectively removed tested contaminants. In this work, a biochar based composite material with AlOOH nano-flakes was fabricated from AlCl3 pretreated biomass through slow pyrolysis in a N2 environment at 600°C. Physicochemical properties of the biochar/AlOOH nanocomposite were studied systematically with several commonly used material characterization instruments, including electron microscopes and X-ray techniques. Structure and morphology analysis of the sample showed that the AlOOH particles/flakes are nanosized and uniformly grow on the carbon surface within the pores of the biochar. Laboratory batch sorption experiments were conducted to evaluate the sorption ability of the biochar/AlOOH nanocomposite to three representative aqueous contaminants: arsenic, methylene blue, and phosphate. The adsorption isotherm and adsorption kinetics data suggested that the biochar/AlOOH nanocomposite is an excellent multifunctional adsorbent that can effectively remove all these contaminants from aqueous solutions.